POI06 Rituximab in neuropsychiatric systemic lupus erythematosus: a retrospective study of the Cambridge experience. Issue 11 (22nd October 2010) - Zandi, M; Catapano, F; Burns, S; Hall, F C; Smith, K G C; Jayne, D R W; Coles, A J
Abstract : The monoclonal B cell depleting antibody, rituximab, has shown promise in open-label studies of refractory neuropsychiatric (NP) lupus. Here, we show our tertiary referral centre experience in patients with CNS syndromes probably causally related to active SLE, and in those with past CNS symptoms treated for non-NP SLE. Consensus criteria proposed by Hanly et al (Arth Rheum 2007) were used to classify patients into those likely to have attributable disease or not. Some patients have been previously reported (Smith et al Arth Rheum 2006). Four patients received rituximab for CNS symptoms attributable to active lupus (two psychosis, one neuropsychiatric syndrome, one neuromyelitis optica). The baseline clinical, imaging and laboratory features, clinical responses and adverse events are reported. A summary is provided of our other patients given rituximab for active non-NP SLE, with previous possible attributable NP disease, including anti-phospholipid syndrome. All patients had other organ disease, received prior and concomitant immunotherapy, and most were retreated. Rituximab appears effective with attributable disease and limited prior damage, with limited effect on symptoms due to static deficits. A randomised, double-blind placebo-controlled trial of rituximab, in patients with early attributable disease and limited established damage, is required. There is also a need to study the natural history of NP involvement in SLE and discover and develop biomarkers to aid attribution.